2021
DOI: 10.1021/acs.joc.1c01132
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dibenzotropones by Alkyne-Carbonyl Metathesis

Abstract: Dibenzocycloheptanones (dibenzotropones) were prepared by Brønsted acid mediated intramolecular alkyne-carbonyl metathesis (ACM) reactions. The cyclization precursors are readily available by Sonogashira reaction of 2-bromobenzoyl chloride with terminal alkynes, followed by Suzuki reactions with benzaldehydes. The ACM reactions are highly modular and atom economic and allow for the construction of two regioisomeric series of dibenzotropones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
(76 reference statements)
0
17
0
Order By: Relevance
“…Finally, the intramolecular ACM reaction was studied and the conditions were optimized for derivative 5a (Table 4). As in previous studies of our group, 12 we focused on the use of Brønsted acids, such as para -toluenesulfonic acid (PTSA), methanesulfonic acid (MSA) and trifluoroacetic acid (TFA). While TFA gave no conversion of the starting material, both sulfonic acids gave the desired ACM product in moderate yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the intramolecular ACM reaction was studied and the conditions were optimized for derivative 5a (Table 4). As in previous studies of our group, 12 we focused on the use of Brønsted acids, such as para -toluenesulfonic acid (PTSA), methanesulfonic acid (MSA) and trifluoroacetic acid (TFA). While TFA gave no conversion of the starting material, both sulfonic acids gave the desired ACM product in moderate yields.…”
Section: Resultsmentioning
confidence: 99%
“…8 In recent years, the alkyne-carbonyl metathesis (ACM) reaction, promoted by either Lewis acid 9 or Brønsted acid, 10 has been used as an alternative to more classical olefination reactions in the synthesis of carbocycles, heterocycles, and polycyclic aromatic frameworks. 11,12 For example, Jana et al reported the synthesis of seven-membered rings, such as dihydrobenzo[ b ]azepines, dibenzo[ b , f ]oxepines and benzo[ b ]oxepines, by iron( iii ) chloride-catalyzed intramolecular alkyne–carbonyl metathesis. 11 b , c Herein, we wish to report a new approach to imidazo[1,2- a ]azepines via Brønsted acid mediated ACM reactions (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…Maryan Sobhani, a Ph.D. student and DAAD scholar from Iran, studied the application of the ACM reaction to the synthesis of two regioisomeric series of naphthothiophenes. 22 The Suzuki–Miyaura reaction of 2,3-dibromothiophene ( 33 ) with (2-formylphenyl)boronic acid ( 15a ) and subsequent Sonogashira reaction with phenylacetylene afforded 34a (Scheme 9 ). Subsequent ACM reaction in the presence of PTSA (toluene, 100 °C, 1 h) afforded naphtho[1,2- b ]thiophene 35a .…”
Section: Naphthothiophenesmentioning
confidence: 99%
“…[49] This reaction has a poor efficiency for two reasons: first, it is a twostage yield, and second, the outcome is so dependent in the substitutions of aldehyde and acid substrates that only the electron donor groups help the process continue faster. [49] Furthermore, although the authors proposed a different pathway, this kind of reaction is promoted by a Lewis or Brønsted acid to catalyze the alkyne-carbonyl metathesis [50] via the formation of a 2H-oxete 85, followed by its rearrangement to give the target product 86, as shown in Scheme 29.…”
Section: Chemistryselectmentioning
confidence: 99%